Side Group Engineering of Small Molecular Acceptors for High‐Performance Fullerene‐Free Polymer Solar Cells: Thiophene Being Superior to Selenophene. (19th July 2017) - Gao, Wei; An, Qiaoshi; Ming, Ruijie; Xie, Dongjun; Wu, Kailong; Luo, Zhenghui; Zou, Yang; Zhang, Fujun; Yang, Chuluo
Abstract : Side group of ITIC‐like small molecular acceptor (SMA) plays a critical role in crystallization property. In this article, two new SMAs with n ‐hexylthienyl and n ‐hexylselenophenyl as side chain, namely ITCPTC‐Th and ITCPTC‐Se, are designed and synthesized by employing newly developed thiophene‐fused ending group (CPTCN). And thiophene and selenophene side group substituted effects of SMA‐based fullerene‐free polymer solar cells (PSCs) are investigated. A stronger σ‐inductive effect between selenophene side group and electron‐donating backbone endows ITCPTC‐Se with better optical absorption and higher LUMO level, ITCPTC‐Th‐based PSCs deliver a higher power conversion efficiency of 10.61%. Charge transport and collection, recombination loss mechanism, and morphology of blend films are intensively studied. These results confirm that side group substituted effects of SMAs are multiple and thiophene is a superior option to selenophene as aromatic side group of ITIC‐like SMAs. Abstract : Two new small molecular acceptors (SMAs), ITCPTC‐Th and ITCPTC‐Se, are designed and synthesized to investigate thiophene and selenophene side group substituted effects. A polymer solar cell (PSC) based on ITCPTC‐Th achieves high power conversion efficiency (PCE) of 10.61%, which are significantly higher than that of ITCPTC‐Se‐based PSC. This confirms that thiophene is superior to selenophene as side group of ITIC‐like SMAs.